Translation Theories and Their Implications for Scientific Text Translation: An Analytical Application - Rumbardi Rumbardi; Imelda Indah Lestari (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
Scientific text translation presents challenges that extend beyond linguistic equivalence. It requires translators to balance accuracy, clarity, terminological consistency, and disciplinary conventions. This article reviews major translation theories proposed by Nida, Catford, Newmark, Reiss, Vermeer, House, Nord, Baker, Lefevere, and Venuti, and examines their implications for the translation of scientific discourse. Drawing on selected examples from biomedical and engineering texts, the study demonstrates how theoretical perspectives can guide translation strategies that ensure both fidelity and functionality. The analysis shows that no single theory is sufficient to address the complexity of scientific translation. Instead, a hybrid approach that combines linguistic, functionalist, textual, pragmatic, and ethical perspectives offer a more effective framework. Such an approach helps translators maintain terminological precision, improve textual coherence, adapt structures to target-language conventions, and preserve the communicative purpose of scientific knowledge.